A Study of Anti Microbial Resistance in Salmonella Enterica Serovars Typhi and Paratyphi A At CMH Quetta - Nasir, Haseeb; Shabbir, Hassan; Tayyab, Nadia; Abbas, Sayed Tanveer; Zafar, Maryam (Pakistan Armed Forces Medical Journal, 2025)
Objectives: To ascertain the antimicrobial resistance of Paratyphi A and Typhi Serovars of Salmonella EntericaStudy Design: Prospective Observational StudyPlace and Duration of Study: Clinical Microbiology Laboratory at the CMH Quetta November 2022-Septmeber 2023Patients andMethodology: The data from the lab were reviewed in this investigation Blood cultures from 1441 admitted patients from the Medicine department supplied to the laboratory of the CMH Quetta between November 2022 and September 2023 were tested for antibiotic susceptibility and Typhoidal Salmonellae were isolated.Results: Out of total 1441 isolates, 839(58.2%) were isolates of Salmonela Typhi and 602(41.8%) were S Paratyphi .These microbes had maximum resistance against Ceftriaxone (71.6%, 67.2%), Ciprofloxacin (70.6%, 66.6%). S typhi and paratyphi have minimal resistance to Meropenum 7.7% and 9.13% respectively. These patients had maximum sensitivity for Meropenum.Conclusion: S. Typhi and S. Paratyphi have high rates of multidrug resistance against Ceftriaxone and Ciprofloxacin. Meropenum had found to have minimal resistance.